Sustainability and Equity Challenges : Some Arithmetic on Lebanon's Pension System - Jarmuzek, Mariusz; Nakhle, Najla (Washington, D.C. : International Monetary Fund, 2016)
Reform of Lebanon's pension system is indispensable. The country already faces fiscal sustainability risks, which will be compounded in the future by significantly higher pensionrelated spending and liabilities, mainly reflecting adverse demographics. In addition to sustainability issues, the pension system also suffers from equity shortcomings-Lebanon is the only MENA country that does not offer social security for retirees in the private sector. While several reform proposals have been formulated since the early 2000s, none has been implemented to date. Costs mount with every year of delay, so action is required soon to address these challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet